Analysis of Patient Satisfaction and Loyalty Mediated by Reputation and Conduct of Public Hospital Staff Government of North Sumatra Province - Nasution, Sri Lestari Ramadhani; Sitompul, Fernades; Wienaldi, Wienaldi; Girsang, Ermi (Poltekita : Jurnal Ilmu Kesehatan, 2024)
This research investigates the pivotal role of hospitals in healthcare, categorizing them into general and specialized facilities based on resources and capabilities. Focusing on North Sumatra, the study explores the significance of hospital conditions in influencing patients' choices, particularly in a competitive healthcare landscape driven by responsiveness to quality information. Employing a quantitative approach with non-probability sampling, the research follows a positivist philosophy to examine the connection and influence between independent and dependent variables. Conducted at the General Government Hospital in North Sumatra, the study spans from a preliminary survey in September 2023 to November 2023, with data collection ongoing and results to be presented in a seminar. The analysis reveals a substantial impact of Patient Satisfaction (PS) on Patient Loyalty (PL) (coefficient = 0.581), supported by a t-statistic value of 5.572 (>1.96) and a p-value of 0.000 (<0.05). PS also significantly influences Hospital Staff Behavior (HSB) (coefficient = 0.280, t-statistic = 2.630, p-value = 0.009 < 0.05) and Hospital Reputation (HR) (coefficient = 0.450, t-statistic = 4.789, p-value = 0.000 < 0.05). Hospital Staff (HS) demonstrates a notable influence (coefficient = 0.101) on PL, though the relationship is not statistically significant (t-statistic = 1.520, p-value = 0.129 > 0.05). Similarly, HR influences PL (coefficient = 0.124), but the relationship is not statistically significant (t-statistic = 1.402, p-value = 0.161 > 0.05). Furthermore, PS exhibits a mediated influence on PL through HSB (coefficient = 0.028, t-statistic = 1.221, p-value = 0.223 > 0.05) and through HR (coefficient = 0.056, t-statistic = 1.269, p-value = 0.205 > 0.05). These findings underscore the critical role of patient satisfaction in shaping loyalty, highlighting the mediating effects of Hospital Staff Behavior and Hospital Reputation. Understanding these dynamics is crucial for promoting healthcare competition and enhancing care quality in the North Sumatra region.